Islamic Banks and Financial Stability: A Comparative Empirical Analysis - Hua, Jingyi (2020)
The study intends to investigate whether Islamic banks have less or more financial stability than commercial banks, using regressions of z-scores as a function of dependent variables. The comparative analysis is performed by identifying whether factors established in the capital structure, cost efficiency, bank size and economy are relevant in explaining the financial stability in the banking industry, covering a time dimension of 8 years from 2012 to 2019. This analysis starts by adopting the random- effects panel regression model with the default risk, leverage risk and portfolio risk as dependent variables and bank-specific and country-specific indicators as explanatory variables. The result of the study reveals that (i) the financial stability of large Islamic banks is discovered better than large conventional banks; (ii) the financial stability of small Islamic banks tend to be weaker than small conventional banks. The comparative analysis of Islamic sample and conventional sample implies differences in the potential of absorbing shocks as well as the state of financial stability. And then critical discussions are followed up on the causes of these differences.